Effect Of Showing Density And Shelter On The Survival And Growth Of Freshwater Losbter Seeds (Cherax quadricarinatus) - Andriyeni Andriyeni; Zulkhasyni Zulkhasyni; Gita Anggraini; Dedi Pardiansyah; Yufiperius Yufiperius (University of Prof. Dr. Hazairin, SH, 2023)
The problem that is often faced by crayfish cultivators at the moment is the low survival rate, especially when the seeds are also stocking density which is not known with certainty, especially during nursery activities and rearing of crayfish (Cherax quadricarinatus). This research was conducted for 60 days in Sukaraja District, Seluma Regency. This study aims to determine the effect of stocking density and shelter and interactions on the survival and growth of freshwater crayfish (Cherax quadricarinatus) fry. The study used a completely randomized factorial design with three replications. The first factor was stocking density consisting of A1 = 6 individuals (48/m²), A2 = 7 individuals (59/m²), and A3 = 8 individuals (68/m²). and the second factor is the shelter which consists of B1 = paralon pipe, B2 = roster stone and B3 = bamboo. If there is a significant effect, then the Duncant Multiple Range Test (DMRT) is carried out. The results showed that the stocking density treatment had a very significant effect on survival, molting percentage, absolute weight and absolute length but had no effect on feed conversion and feed efficiency, while the shelter treatment had no significant effect on all observed parameters. The interaction effect of stocking density and shelter treatment had a significant effect on absolute weight growth but had no effect on survival, moulting percentage, absolute length, feed conversion and feed efficiency. Stocking density of 6 individuals/48/m² container and paralon pipe shelters gave the best results for survival and growth of crayfish (Cherax quadricarinatus).